Development of Automobile Scaled Model from CAD (Blender) Using FDM 3D Printing - Aditi Ajit Patil; Shetty Shravan Venugopal; Prof. Ameya Nijasure (International Journal of Advanced Control and System Engineering, 2024)
Additive manufacturing (AM), also known as 3D printing, has emerged as a disruptive technology with the potential to transform automotive manufacturing. This paper reviews the applications of AM across the automotive product development lifecycle. The paper examines case studies demonstrating the use of AM for developing computer-aided design (CAD) models from concept sketches. Overall, AM brings several benefits such as design flexibility, faster time-to-market, and distributed production. However, there are also limitations around part quality, materials, and costs. Blender is used as a CAD tool to explore various tool kits, freeform shape modeling techniques for an automobile prototype. Ultimaker fused deposition modeling (FDM) 3D printing is used to print prototypes of 1:10 scale. AM facilitates rapid prototyping and tooling, enabling faster design iteration and concept validation. This paper provides a holistic analysis of the role of AM in the automotive industry, including its capabilities, benefits, and challenges. The review will help automotive firms effectively leverage AM to enhance manufacturing agility, productivity, and innovation. In this article, the creation of a scaled car model that was created with Blender for 3D modeling and printed using FDM is examined. From CAD design in Blender to the actual model's realization through AM, the paper outlines the procedures involved. Important factors, including layer height, print optimization, and material selection are covered. FDM's effectiveness in quick prototyping and model manufacturing for the automobile industry is validated by the results, which show the scaled model's correctness and structural integrity. The ramifications for upcoming developments in 3D printing technology in vehicle prototyping are examined in the article's conclusion.
Keywords: 3D printing; Additive manufacturing; Blender; Fused Deposition Modeling (FDM); Modeling; automotive design